Keabsahan Scientific Crime Investigation sebagai Alat Bukti dalam Proses Pembuktian Perkara Pembunuhan - Isti Puspitasari (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
The purpose of this research is to examine and analyze the validity of scientific crime investigation as evidence in the process of proving murder cases and what are the advantages and disadvantages of using the scientific crime investigation method in crime scene processing carried out by forensic laboratories. Then the method used in this research is the normative legal research method. The results of the study show that the scientific crime investigation method, which is expressed in concrete form through forensic laboratory examinations and information from police forensic experts, is the central point. In connecting the relationship between the perpetrator, victim and evidence with the crime scene, the construction of evidence for a criminal act becomes stronger and can give confidence to the judge in deciding a case fairly and in accordance with the actual facts. In the case of the crime of murder with poison, the statements of the witnesses and the statements of the two defendants were linked and interconnected with each other after the scientific crime investigation method was applied; The advantages and disadvantages of using scientific crime investigation methods in crime scene processing carried out by forensic laboratories include. The advantages and disadvantages of using scientific crime investigation methods in crime scene processing carried out by forensic laboratories include: (1). The advantage of implementing scientific crime investigation is that uncovering cases using old methods full of violence, intervention, etc. has been abandoned. (2) Fast, precise and accurate inspection supported by special tools that have been internationally standardized, (3) Minimizing errors made before SCI implementation (manual patterns replaced with digital patterns). Meanwhile, the weaknesses are: Internal side of the SatKer (Work Unit): the number of human resources who supervise and understand the use of Special Tools (Alsus) is limited, the special equipment, both primary and secondary, is expensive. If we look at the human resources that this country has, it should be enough to assist the Forensic Laboratory team in supervision and are people who understand the special tools that support the performance of the Forensic Laboratory. Apart from that, the government should be more respectful of the procurement of these special tools, even though not everyone has to always use these special tools. However, these tools are very useful for the smooth running of investigations and/or investigations. Because the resulting examination data is much more detailed and accurate.